A framework for examining the dimensions and characteristics of complexity inherent within rail megaprojects. Issue 6 (August 2016) - Chapman, Robert J.
Abstract: This paper presents a framework for examining the dimensions and characteristics of project complexity, with an emphasis on rail megaprojects. UK government departments have recorded that project complexity has increased significantly over the last decade and highlight that the subject has received inadequate attention, with a detrimental effect on project performance. However departments have not examined the characteristics of complexity or made a distinction between complexity emanating from the decisions made by the project itself and the complexity emanating from its context, as they warrant different treatment. By way of response, post examination and comparison of existing frameworks, a new framework is proposed based on a literature review. A case study is examined to illustrate how the framework may be applied. Highlights: Suitable dimensions of complexity for rail megaprojects include finance, management, context, task, site and delivery A distinction needs to be made between complexity under the control of the project and complexity imposed by the context Management of complexity is a determinant of project success The nature of complexity of a project is not static but dynamic due to for instance the effectiveness of project initiation, the evolving maturity of project management practices, the application of assurance processes and project governance Complexity frameworks for rail projects need to include the complexity dimension of site